Usefulness of determination of glucosylisomaltol and hydroxymethylfurfural to control browning reaction during storage of baby cereals Utilidad de la determinación de glucosilisomaltol e hidroximetilfurfural para el control de la reacción de pardeamiento durante la conservación de cereales infantiles (2011)
ABSTRACT: Glucosylisomaltol (GIM) and hydroxymethylfurfural (HMF) were determined in gluten and gluten-free baby cereals stored under industrial conditions for 1 year and under laboratory conditions for 1 month at Aw 1⁄4 0.65. In eight mixed cereals, GIM was detected at all times and temperatures assayed, increasing during storage. In rice cereals, GIM was only detected under industrial conditions after 3 and 6 months of storage at 55 and 32 8C, respectively; at Aw 1⁄4 0.65, GIM was detected after 1 week of storage at 25 and 55 8C. In storage of rice–corn cereals under industrial conditions, GIM was only detected at 55 8C; under laboratory conditions, GIM was detected after 1 week at 55 8C and after 3 weeks of storage at 25 8C. HMF decreased during storage of baby cereals except in rice cereals, the only sample without caramel as an ingredient. HMF only proved to be a useful indicator in rice cereals, whereas GIM was useful in all samples.